The Correlation between Blood Lead Levels and Smoking Habits among Retail Gasoline Sellers - Mahdiah Syumarliyanty; Tri Harningsih (Indonesian Journal of Global Health Research, 2025)
Heavy metal lead (Pb) is a type of metal that can negatively impact both the environment and human health. With a melting point of 327.5ºC, lead is a naturally occurring element in the Earth's crust. Lead can enter the human body through various means, including water, soil, and air. Inhalation is one of the primary routes of lead exposure. Lead levels in the body can be assessed through blood, bones, hair, and nails. Additionally, smoking habits can influence blood lead levels, as cigarette smoke contains small amounts of lead. This study aims to examine the relationship between blood lead levels and smoking habits among retail gasoline sellers. A descriptive-analytical research approach was employed, using a cross-sectional design and purposive sampling technique. The study subjects comprised retail gasoline sellers in Batu Ampar sub-district, Balikpapan City, who met the inclusion criteria. Blood samples were analyzed using the ICP-OES method at the Labkesda DKI Jakarta. Data analysis was conducted using the non-parametric Spearman test. The results from 20 respondents indicated no statistically significant relationship between blood lead levels and smoking habits among retail gasoline sellers in Batu Ampar sub-district, Balikpapan City (correlation value = 0.115, p-value = 0.628). The highest recorded blood lead level among daily smokers was 8.634 µg/dL, while the lowest was <0.228 µg/dL.